ANALISIS PENGARUH JUMLAH ARMADA, JUMLAH NELAYAN, PDRB, DAN INVESTASI TERHADAP PRODUKSI PERIKANAN DI WILAYAH NIAS (ANALISIS DATA PANEL) - Nike Deliyanti Zebua; Ramli Ramli (Departemen Ekonomi Pembangunan USU, 2014)
This research aims to analyze the effect of the number of fleets, the number of fisherman, GDP, and investment to the production of fisheries in the region of Nias. The data used in this research is secondary data which is obtained from Badan Pusat Statistik and Dinas Perikanan. The sample consists of five regencies/city, including Regency of Nias, Regency of Nias Selatan, Regency of Nias Utara, Regency of Nias Barat, and Gunungsitoli.This research used the method of Panel Data Analysis which is based on five years observation, from 2008 to 2012. The result of this research showed that the number of fleet and the number of fisherman have a positive and significant effect to the production of fisheries in the region of Nias. GDP has a negative and significant effect to the production of fisheries in the region of Nias. While investment has a negative and insignificant effect to the production of fisheries in the region of Nias. The result of Chow test and Haussman Test show that the best method to use is FEM. Based on difference test among variables can be seen that there is difference of fishery production among the regencies of Nias.Keywords: Production of Fisheries, The Number of Fleet, The Number of Fisherman, GDP, Investment, Water Production